MEMAHAMI gambaran mikroanatomi pada operasi bedah saraf / Muhammad Zafrullah Arifin...[et al] ; editor, Genis Ginanjar ; ilustrasi, M. Mukhlis F.A. - Muhammad Zafrullah Arifin; Genis Ginanjar; Mukhlis F.A., M. (Sagung Seto, 2012)
vii, 86 hlm. : ilus. ; 21 cm [3 eks.]